تقويم مدى تبني الثقة التنظيمية لدى أعضاء الهيئة التعليمية في جامعة تشرين ( دراسة مسحية) - ديب كندة; زعتر نيفين (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدفت هذه الدَراسة إلى تقويم تبني مفهوم الثقة التنظيمية في جامعة تشرين، حيث استخدمت الباحثة المقاربة الاستنباطية كمنهج عام للبحث، وقد تمَ توزيع الاستبيان على 370 فرد من أعضاء الهيئة التعليمية في جامعة تشرين، ومن ثمَ أُجريت الدَراسة الميدانية في الجامعة. وقد خلصت الدَراسة إلى أنه يوجد فروق جوهرية بين مستوى الثقة كأحد أبعاد رأس المال الاجتماعي السائدة حالياً في الجامعة محل الدراسة, وبين مستوى الثقة الواجب توافرها في الجامعة محل الدَراسة. ثم قدًمت ملخص لأهم النتائج التي تمَ التوصل إليها، حيث تبيَن أنَ أعضاء الهيئة التعليمية في الجامعة لديهم ثقة بإدارة الجامعة وبالمشرفين وبزملاء العمل، ثم تمَ عرض بعض المقترحات والتوصيات والتي أهمها(يجب الاهتمام بتعزيز العلاقة بين إدارة الجامعة وأعضاء الهيئة التعليمية وتطويرها من خلال تكثيف اللقاءات والاجتماعات التوجيهية. This study aimed to evaluating the adoption of the concept of organizational trust in Tishreen University, where the researcher used the approach of development as a general approach to research. The questionnaire was distributed to 370 members of the faculty at Tishreen University, The field study was then conducted at the university. The study found that there are significant differences between the level of trust as one of the dimensions of social capital currently prevailing in the university in question, And the level of trust required to be available at the university in question. And then presented a summary of the most important findings, , Where it was found that members of the teaching staff at the university have confidence in the university administration and supervisors and colleagues work. Some suggestions and recommendations were presented, the most important of which are: (i) Attention should be given to strengthening the relationship between the university administration and the members of the educational body through the intensification of meetings and orientation meetings.